Nutrition in Pediatric Intensive Care: A Narrative Review - Kratochvíl, Milan; Klučka, Jozef; Klabusayová, Eva; Musilová, Tereza; Vafek, Václav; Skříšovská, Tamara; Djakow, Jana; Havránková, Pavla; Osinová, Denisa; Štourač, Petr (Children (Basel, Switzerland), 2022)
Nutrition support in pediatric intensive care is an integral part of a complex approach to treating critically ill children. Smaller energy reserves with higher metabolic demands (a higher basal metabolism rate) compared to adults makes children more vulnerable to starvation. The nutrition supportive therapy should be initiated immediately after intensive care admission and initial vital sign stabilization. In absence of contraindications (unresolving/decompensated shock, gut ischemia, critical gut stenosis, etc.), the preferred type of enteral nutrition is oral or via a gastric tube. In the acute phase of critical illness, due to gluconeogenesis and muscle breakdown with proteolysis, the need for high protein delivery should be emphasized. After patient condition stabilization, the acute phase with predominant catabolism converts to the anabolic phase and intensive rehabilitation, where high energy demands are the keystone of a positive outcome.
Keywords: nutrition; child; nutrition support; intensive care; enteral feeding; parenteral nutrition; pediatric